Enhancing 8th grade students' mathematical understanding: A quasi-experimental study on game-based learning media - Dian Fulana; Fitria Zana Kumala (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
The low mathematical comprehension among 8th-grade students at MTs Al-Hidayah Purwokerto drove this research. Factors contributing to this low ability include the use of conventional learning media, which is less attractive to students, leading them to easily become bored and encounter greater difficulty in understanding lessons. Therefore, this study aimed to evaluate the efficacy of using educational game-based learning media to enhance students' mathematical understanding skills in 8th grade. An experimental approach was employed in this study, with a population consisting of 56 students from the 8th grade at MTs Al-Hidayah Purwokerto. Saturated sampling was conducted, encompassing all 8th-grade students as the research sample. Consequently, Class 8A, comprising 28 students, was designated as the experimental group, while Class 8B, with 28 students, served as the control group. The research's conclusive outcomes indicate that using educational game-based media effectively improves students' mathematical understanding abilities. The N-Gain value for the experimental group is 0.83, which falls within the high category, whereas the N-Gain value for the control group is 0.37, categorized as medium. Thus, it can be inferred that educational game-based media is effective as a learning medium for 8th-grade mathematics material at MTs Al-Hidayah Purwokerto.